Unpredictable Nanoparticle Retention in Commonly Used Plastic Syringes Introduces Dosage Uncertainties That May Compromise the Accuracy of Nanomedicine and Nanotoxicology Studies - Holzwarth, Uwe; Cossío, Unai; Llop, Jordi; Kreyling, Wolfgang G. (Frontiers in Pharmacology, 2019)
The investigation of the interaction of nanomaterials with biological systems appears to be especially affected by a lack of reproducibility and comparability of data. This triggered a lot of efforts to harmonize the execution and reporting on experimental studies and to improve the reproducibility, credibility and efficiency of scientific research. These efforts comprise the set-up of repositories of well-characterized representative industrially manufactured nanomaterials, the development of reference materials and the recommendation of Minimum Information Reporting in Bio-Nano Experimental Literature (MIRIBEL). Unfortunately, these efforts are still incomplete. The present study illustrates that the retention of nanoparticles in disposable plastic syringes may lead to non-neglectable dosage uncertainties in in vivo studies. This error source is still not covered by MIRIBEL, and from the lack of reporting in literature one has to conclude that this error has been neglected in so far published in vivo studies dealing with nanomaterials. In animal experiments using suspensions of radiolabeled nanoparticles large and highly variable radioactivity fractions were retained in disposable plastic syringes after unloading. This implies that the effectively delivered nanoparticle dose to the animals was frequently much smaller than the nominal dose of the nanoparticles loaded into the syringe which is usually set as applied nanoparticle dose. A control study employing six commonly used syringe types with seven types of radiolabeled oxide and metallic nanoparticles and data gathered from in vivo animal imaging studies, including radiolabeled exosomes, polymersomes and protein-based nanoparticles, shows that nanoparticle retention in syringes depends on the combination of the nanoparticle suspension and the syringe type. Since this retention is highly variable the problem cannot be handled by applying a simple retention factor. For very unfavorable combinations it is not possible to predict whether e.g. 7% or 79% of the nanoparticles will be retained in the syringe. The present work shall illustrate the problem and proposes as mitigation strategy adequate checks with different syringe types in order to find out whether a given nanoparticle suspension is affected by nanoparticle retention and, if necessary, to select a syringe type that minimizes retention.